Ductal Carcinoma In Situ: What the Pathologist Needs to Know and Why - Anita Bane (International Journal of Breast Cancer)
Ductal carcinoma in situ is a proliferation of malignant epithelial cells confined to the ductolobular system of the breast. It is considered a pre-cursor lesion for invasive breast cancer and when identified patients are treated with some combination of surgery, +/− radiation therapy, and +/adjuvant tamoxifen. However, no good biomarkers exist that can predict with accuracy those cases of DCIS destined to progress to invasive disease or once treated those patients that are likely to suffer a recurrence; thus, in the era of screening mammography it seems likely that many patients with DCIS are overtreated. This paper details the parameters that should be included in a pathology report for a case of DClS with some explanations as to their importance for good clinical decision making.